Oral health care education and its effect on caregivers’ knowledge and attitudes: a randomised controlled trial - Frenkel HF, Harvey I, Needs KM. (Blackwell Synergy, 2002)
The effect of an oral health care education programme (OHCE) upon nursing home caregivers was assessed in a randomised controlled trial.